Employment, Growth and development : a post-Keynesian approach - Gnos, Claude; Rochon, Louis-Philippe; Tropeano, Domenica (Cheltenham Edward Elgar Publishing Ltd., 2012)
Summary: Bringing together over a dozen post-Keynesian experts on the issue of employment, growth, development and exchange rates, this book breaks new ground by offering interesting and innovative insights into the problems faced today in both developed and developing countries. This topical book addresses unemployment in Europe, the wrong-headed reliance on NAIRU to formulate policy, distributional conflicts and financial factors, as well as problems faced in developing countries with respect to exchange rate policy, central banking, challenges to growth, and international financial flows. In the first part of the book the chapters deal with issues related to employment policies, economic growth and development while the second part is dedicated to development and growth issues in open-economy developing countries. Employment, Growth and Development offer an interesting analysis of the current economic issues from a post-Keynesian perspective that will appeal to academics and graduate students interested in development and economics
Introduction: post- Keynesian economic policy - a post- crisis view / Claude Gnos, Louis-Philippe Rochon and Domenica Tropeano --
PART I: LABOR, EMPLOYMENT POLICIES AND DISTRIBUTION
1. Deconstructing Labor: What is 'New' in Contemporary Capitalism and Economic / Policies Riccardo Bellofiore and Joseph Halevi --
2. Breaking the Economic Dependence of Developing Countries to Promote Economic Development and Full-Employment: The Case of the Maghreb Countries / Mehdi Ben Guirat and Corinne Pastoret --
3. The Redistribution Conflict in the 'Patrimonial Regime' through a Stock - Flow Consistent Model / Mickael Clevenot and Yann Guy --
4. Income Distribution, Growth and Financialization: The Italian Case / Domenica Tropeano --
5. Faith-based Macroeconomics: A Critique of Recent Developments in NAIRU estimation / Dany Lang and Mark Setterfield --
6. Still Unemployed, After All These Wage Cuts: Labor in Europe / Engelbert Stockhammer --
7. Labour Market and Monetary Macroeconomics/ Vincent Vernay --
PART II: GROWTH, DEVELOPMENT AND EXCHANGE RATES
8. Exchange Rate Policy in Developing Countries: The East Asian Experience / Mohamed Aslam --
9. A Keynesian-Structuralist Growth Strategy for Latin America / Julio Lopez and Fernando J. Cardim de Carvalho --
10. Financial Market Development and Economic Growth through a post-keynesian lens: Hong konk case study / Taha Chaiechi --
11. Money and Institutions: The Long Path of the Latin American Financial Reforms / Eugenia Correa --
12. The Effect of Interest Rates in Developing Countries: Can Central Bank Monetary Policy Instruments Modify Economic Growth? / Noemi Levy Orlik
13. International Capital Flows and Latin America: Making Sense of Disappointing Results / Wesley C. Marshall --
14. Inflation Targeting by the 'Tyrannical Auctioneer': the Predominance of a Normative Approach in Monetary Policy / Etelberto Ortiz Cruz --
Summary from the back cover of the book.
Includes bibliographical references and index.
Keywords: Macroeconomics; EMPLOYMENT; ECONOMIC THEORY; EMPLOYMENT GROWTH; KEYNESIAN ECONOMICS; ECONOMIC DEVELOPMENT